The Conflict of Aerodynamic Efficiency and Static Longitudinal Stability of Box Wing Aircraft - Daniel Schiktanz and Dieter Scholz (2011)
The induced drag of box wing aircraft is assessed with the help of literature data. The theoretical foundations of static longitudinal stability and controllability are presented and applied to the box wing aircraft. The results are interpreted and put into practice with the help of a medium range box wing aircraft based on the Airbus A320. Stability in cruise is attained by increasing the ratio C_L,1/C_L,2 to a value of 1.74, which is the ratio of lift coefficients of the forward and the aft wing. According to biplane theory this results in a 3.4 % increase of induced drag. Applying aerodynamic theory for closed wing systems no increase would be expected. With the stated ratio of lift coefficients results a relatively small envelope for the center of gravity (CG). Consequently the aircraft is designed to be well balanced with regard to its CG. The individual CGs of the airframe, engines, fuel and payload are all located approximately at the same position. Hence the CG shift is minimized for different payload and fuel quantities.
Keywords: box wing; static longitudinal stability; induced drag; aerodynamic efficiency